A novel testis-enriched gene, Samd4a, regulates spermatogenesis as a spermatid-specific factor - Ahn, Jinsoo; Kim, Dong-Hwan; Park, Mi-Ryung; Suh, Yeunsu; Lee, Haesun; Hwang, Seongsoo; Mamuad, Lovelia L.; Lee, Sang Suk; Lee, Kichoon (Frontiers in Cell and Developmental Biology, 2022)
Spermatogenesis is the highly orchestrated process involving expression of a series of testicular genes. Testis-enriched genes are critical for cellular processes during spermatogenesis whose disruption leads to impaired spermatogenesis and male infertility. Nevertheless, among poorly investigated testicular genes are the mouse Samd4a and human SAMD4A which were identified in the current study as novel testis-enriched genes through transcriptomic analyses. In particular, as orthologous alternative splicing isoforms, mouse Samd4a E-form and human SAMD4A C-form containing the SAM domain were specific to testes. Western blot analyses revealed that the murine SAMD4A E-form was predominantly found in the testis. Analyses on GEO2R and single-cell RNA-seq datasets revealed that the Samd4a/SAMD4A expression was enriched in spermatids among various types of cells in adult testes. To investigate in vivo functions of Samd4a, Samd4a knockout mice were generated using the CRISPR/Cas9 system. The Samd4a deficiency resulted in lower testis weight, absence of elongated spermatids, and an increased number of apoptotic cells. Profiling of gene expression in human testis samples revealed that the SAMD4A expression was comparable between obstructive azoospermia (OA) patients and normal controls, but significantly lowered in nonobstructive azoospermia (NOA) patients. Among three subgroups of NOA, pre-meiotic arrest (NOA-pre), meiotic arrest (NOA-mei), and post-meiotic arrest (NOA-post), expression level of SAMD4A was higher in the NOA-post than the NOA-mei, but there was no difference between the NOA-pre and NOA-mei. The current studies demonstrated spermatid stage-specific expression of Samd4a/SAMD4A, and impairment of the late stages of spermatogenesis by disruption of the mouse Samd4a gene. These data suggest that Samd4a/SAMD4A plays an essential role in normal spermatogenesis, and SAMD4A, as a spermatid specific marker, can be used for subcategorizing NOA patients. Further understanding the molecular role of SAMD4A will advance our knowledge on genetic regulations in male infertility.